Analisis Pengaruh Intensitas dan Durasi Hujan Terhadap Stabilitas Lereng pada Tanah Residual Balikpapan - Arief Nugraha Pontoh; Noor Zaqiyah Muhding; Muhammad Fajrin Wahab; Fachreza Akbar (Borneo Engineering: Jurnal Teknik Sipil, 2025)
Rainfall-induced landslides on residual soil slopes pose a serious threat to communities in North Balikpapan, Indonesia, where the landslide hazard index ranges from 0.23 to 0.73 and the region is underlain by weathered residual soils susceptible to slope failure. This study investigates the effects of rainfall intensity and duration on slope stability and pore water pressure in residual soils at three representative sites in North Balikpapan: Institut Teknologi Kalimantan (ITK), Pondok Joang Indah (PJI), and Jalan Sei Wain Km.15. Numerical simulations were performed using SEEP/W for transient seepage analysis and SLOPE/W for slope stability analysis with the Bishop Simplified method, under four rainfall intensity levels (20, 50, 100, and 198 mm/day) and three duration scenarios (1, 2, and 33 hours). Intensity levels were selected based on a 20-year daily rainfall record from the BMKG Sepinggan station (2003-2022), using national rainfall classification categories, with 198 mm/day representing the maximum observed event. Results show that initial safety factors ranged from 0.741 to 3.773 across sites and slope angles. Following rainfall simulation, the Km.15 site with a 35-degree slope transitioned from critical (SF = 1.172) to unstable (SF = 0.894) under 33-hour rainfall. Pore water pressure increased from negative to near-positive values, with maximum infiltration depths of 2.5 m at ITK and 2.9 m at PJI and Km.15, both occurring on the 15-degree slopes, with the greatest effects at slope crests and toes. The 198 mm/day and 33-hour scenario produced the most critical conditions. These findings provide a quantitative basis for rainfall-triggered landslide risk assessment in residual soil areas of Borneo.